The changing dynamics of European electricity markets and the supply-demand mismatch risk - Conall Heussaff; Georg Zachmann (Bruegel, 2024)
Meeting Europe's 2030 climate targets will require massive clean-electricity investment. To facilitate these investments, state-backed de-risking schemes such as contracts for difference (CfDs) are needed. Their role in supporting renewables has been consolidated by the European Union's recently agreed electricity market design reform. Under such state-backed schemes, the distribution of costs between the market and the state will depend on the balance of supply and demand. Lower demand will decrease spot-market prices, reducing market costs but increasing the cost to CfD-issuing states. If electrification of European energy demand does not keep pace with the electricity supply expansion, tens of billions of euros annually could be channelled through state contracts, generating costs that must ultimately be recovered from consumers. A cost-efficient, managed transition will require European coordination of electricity supply, demand and network investments. Clean electricity supply and demand should be synchronised through a combination of state interventions and market mechanisms. Undersupply of clean power will mean a failure to meet climate targets, but oversupply can be costly too. To manage the costs of renewable de-risking schemes and to accelerate energy-system decarbonisation, flexible electricity systems should be promoted, policies to encourage electrification could be implemented and cost-recovery arising from state-backed renewable support schemes should be fair.
Keywords: 330; climate change; European Green Deal